Inside Cover: Fluorine NMR‐Based Screening on Cell Membrane Extracts (ChemMedChem 2/2014). Issue 2 (February 2014) - Veronesi, Marina; Romeo, Elisa; Lambruschini, Chiara; Piomelli, Daniele; Bandiera, Tiziano; Scarpelli, Rita; Garau, Gianpiero; Dalvit, Claudio
<x xml:space="preserve">Abstract</x> The inside cover picture shows how a fluorine‐NMR‐based biochemical assay, known as n‐FABS, can be used to detect high‐ and low‐affinity inhibitors of a membrane‐bound enzyme in cell extracts, with accurate determination of IC50 values from the results. This approach allows the discovery of inhibitors against enzymes that are difficult to purify or where membrane association is required for activity. For more details, see the Communication by Gianpiero Garau, Claudio Dalvit et al. on p. 286 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>